Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/md.0000000000001492
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of C2 Vertebra Screws Placement in Patient With Occipitalization of Atlas

Abstract: Occipitalization of atlas (OA) is a congenital disease with the possibility of anomalous bony anatomies and the C2 pedicle screw insertion is technically challenging. However, there are no existing literatures clarified the dimensions and angulations of the C2 pedicles, lamina and lateral masses for screw insertion in patients with OA. Therefore, the aim of this study was to assess the morphometric features of C2 for screw placement in OA to guide the use of surgical screws.Measurements of the OA patients on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The patients had smaller size of C2 pedicles, Case Reports in Orthopedics particularly on the right side for screw placement. Ji et al [14] describe in their study that the C2 pars/pedicle architectures are significantly smaller in patients with assimilation of the atlas than in the normal population. They suggested that translaminar screw is the more viable option in comparison with pedicle screw for C2.…”
Section: Discussionmentioning
confidence: 96%
“…The patients had smaller size of C2 pedicles, Case Reports in Orthopedics particularly on the right side for screw placement. Ji et al [14] describe in their study that the C2 pars/pedicle architectures are significantly smaller in patients with assimilation of the atlas than in the normal population. They suggested that translaminar screw is the more viable option in comparison with pedicle screw for C2.…”
Section: Discussionmentioning
confidence: 96%
“…Several morphometric studies have investigated the feasibility of the lamina and the spinous process of C2 to admit two crossing screws; many of these studies focused on the size of the lamina, which is a limiting factor for this technique [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Nor should we forget the dimensions of the spinous process as a second limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…The mean PTW is slightly greater on the left side as compared to the right side [2]. However, many CT study concluded in a that there was no significant difference in transverse diameter between the right and left pedicles in both male and female patients [3,12,19]. Therefore, it is important to keep the gender and race of patients in mind when evaluating and planning for transpedicular screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…This accounts for the difference pedicle length reported in those studies. In previous anatomical [9][10][11] as CT evaluation [6,12] reports investigators defined the length as the distance from the posterior surface of the C-2 inferior articulating process to the anterior surface of the vertebral body (range 25.4 mm -28.8 ± 3.4 mm). Howington JU et al [1] chose to define the length as the distance from the posterior surface of the inferior articulating process to the junction of the pedicle with the vertebral body (mean 7.9 mm, range 6.4 to 9 mm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation